2014
DOI: 10.5152/dir.2013.13315
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations in hepatocellular adenoma: an update of MRI findings

Abstract: Hepatocellular adenoma (HCA) is a generally benign liver tumor with the potential for malignancy and bleeding. HCAs are categorized into four subtypes on the basis of genetic and pathological features: hepatocyte nuclear factor 1α-mutated HCA, β-catenin-mutated HCA, inflammatory HCA, and unclassified HCA. Magnetic resonance imaging (MRI) plays an important role in the diagnosis, subtype characterization, and detection of HCA complications; it is also used to differentiate HCA from focal nodular hyperplasia. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…Independently from the subtype, we noted that approximatively 70% of HCA did not display OATPB1/B3 expression. Thus, our results suggest that the “no HBP uptake” criterion proposed in several radiological papers is indeed generally helpful to separate FNH from the majority of HCA . These observations are in accordance with those reported in a systematic review, showing that FNH have iso‐ or high signal, while most HCA has low signal on HBP as compared to the background liver .…”
Section: Discussionsupporting
confidence: 90%
“…Independently from the subtype, we noted that approximatively 70% of HCA did not display OATPB1/B3 expression. Thus, our results suggest that the “no HBP uptake” criterion proposed in several radiological papers is indeed generally helpful to separate FNH from the majority of HCA . These observations are in accordance with those reported in a systematic review, showing that FNH have iso‐ or high signal, while most HCA has low signal on HBP as compared to the background liver .…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that a pooled proportion of fatty degeneration in HCA of 37% (95% CI: 0.27-0.49).The MRI sign is only found in the H-HCA pathological subtype 10. Grazioli L and Purysko AS et al 5-6 reported that fatty tissues are also found in FNH, and could not actually differentiate HCA from FNH just according to the presence of fatty tissues in the tumor 18-19.…”
Section: Discussioncontrasting
confidence: 56%
“…MRI should be preferred in such cases and presence of scar on T2-weighted images and hyperintensity on hepatobiliary phase T1-weighted images after injection of hepatocyte specific agents can be helpful in making the diagnosis (Fig. 8b, 8c) (16,17). Metastasis can mimic focal fat and fat sparing.…”
Section: Mimickersmentioning
confidence: 99%